Oral Administration of Ren-Shen-Yang-Rong-Tang 'Ninjin'yoeito' Protects against Hematotoxicity and Induces Immature Erythroid Progenitor Cells in 5-Fluorouracil-Induced Anemia. Issue 2 (2009) - Takano, Fumihide; Ohta, Yasuyuki; Tanaka, Tomoaki; Sasaki, Kenroh; Kobayashi, Kyoko; Takahashi, Tomoya; Yahagi, Nobuo; Yoshizaki, Fumihiko; Fushiya, Shinji; Ohta, Tomihisa
Abstract : The purpose of this study was to investigate the efficacy of four different Japanese and Chinese herbal prescriptions, Ren-Shen-Yang-Rong-Tang (Ninjin'yoeito, NYT), Chai-Hu-Gui-Zhi-Gan-Jiang-Tang (Saikokeishikankyoto, SKKT), Si-Jun-Zi-Tang (Shikunshito, SKT) and Si-Wu-Tang (Shimotsuto, SMT), which are traditionally used for anemia and fatigue, against hematotoxicity in mice treated with 5-fluorouracil (5-FU). NYT 1–100 mg kg –1 day –1 injected orally for 7 consecutive days before and after 5-FU injection significantly suppressed reductions in red blood cell, white blood cell and platelet counts in peripheral blood, and accelerated their recovery. Administration of SKKT also produced a slight but significant improvement in 5-FU-induced erythrocytopenia, whereas SMT and SKT could not prevent anemia. Oral injection of NYT also inhibited 5-FU-induced decreases in peripheral reticulocyte and bone marrow cell counts on day 10, and markedly hastened their recovery on day 20, in a dose-dependent manner. Erythroid progenitor colonies, such as colony forming units-erythroid and burst forming units-erythroid, formed by marrow cells from mice treated with 5-FU were significantly increased by oral administration of NYT. These findings suggest that NYT has the potential to protect against hematotoxicity, and also has hematopoietic activity, through stimulation of immature erythroid progenitor cell differentiation.